Container networking : from Docker to Kubernetes - Hausenblas, Michael (O'Reilly Media, 2018)
Companies that begin working with containerized applications often aren't prepared for the challenge of container networking. When you want to connect your containerized Python app to a container that has a database, you enter a domain that still demands a good deal of trial and error. This practical ebook delivers basic guidance on container networking with best practices that, until now, have been scattered throughout the web. Michael Hausenblas, a member of Red Hat's OpenShift team, provides developers, site reliability engineers, and software architects with a detailed look at the many challenges of container networking, container orchestration, and service discovery and shares several available solutions. Along the way, you'll learn the capabilities of many open source tools, including Kubernetes. Get an introduction to container networking by exploring single-host Docker networking modes Examine issues that arise when you move to multihost container networking Maintain a map of running containers and their locations with service discovery tools such as ZooKeeper and etcd Configure network interfaces in Linux containers by using plugins with the Container Network Interface (CNI) Learn how the Kubernetes orchestration system approaches container networking.